Entity within - Devon, Cat (New York St Martin's Press, 2013)
Zoe Adams and her grandmother Irma are witches who have been banished from Boston. With nowhere to go, they accept an invitation to come to Chicago ... but what they don't realize is that their new space puts them right in the heart of the most dangerous spot of all: Vamptown. Damon Thornheart is just that--virtually untouchable when it comes to love. As Vamptown's highest-ranking demon hunter, he sees red flags when he meets Zoe and Irma, who unwittingly unleashed a brutal evil upon the community. But the more Damon gets to know the stunning, spirited Zoe, the less he understands about his own true nature. Vamps and witches have always been archrivals in the entity world; surrendering to their passion could mean losing their immortal powers. Is their desire worth the risk? Only one thing is for certain: Damon will make it his mission to find out ...
113173
Keywords: Witches -- Fiction; Vampires -- Fiction; Man-woman relationships -- Fiction; Chicago (Ill.) -- Fiction; Illinois -- Chicago; Paranormal romance stories; Paranormal romance; Fiction